Cultural Activism in Miniature: Exploring the Role of Dolls in the Kenyan Context - Sara Mehrgut (Revista Lusófona de Estudos Culturais, 2024)
This article examines the role of dolls in the history of Kenya, from before colonization to the contemporary era. Dolls, female figures molded by what society dictates as being a woman, are powerful symbols handed down to girls, reflecting cultural and identity values. In pre-colonial societies, dolls were playmates that prepared the girl for societal care or fertility amulets, indicating to the adolescent her responsibility for the community's survival. With colonization came the uprooting and death of many traditions. The few dolls that survived became symbols of resistance against British cultural hegemony, and nowadays, they can be seen as forms of mnemonic activism. Additionally, the arrival of the white doll in the hands of local girls helped many grow trapped in an intricate paradox: they wanted to be seen as beautiful and valuable according to Eurocentric standards while also wishing to celebrate their unique cultural identities. In response to this situation, several Kenyan women entrepreneurs have created modern dolls representing the diversity of the country, but their challenge is to compete in a market where the white doll is always cheaper.